Analysis of Critical Thinking Ability in Solving Story Problems Main Material of Fractional Numbers in View of Student Personality Type - Baharunnisa; Kurniawan, Eka (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2023)
This research aims to determine the level and describe critical thinking abilities in solving story problems on fractional numbers in terms of the personality types of class VII students at SMPN 17 Mataram. This type of research is using mix method. The instrument used is a personality type test, namely a standardized personality testMyers Briggs Type Indicator (MBTI), critical thinking ability tests, and interview guidelines. The sample for this research was class VII-A students, totaling 32 students. From this class, 8 subjects were taken, namely high, medium and low categories for each personality type extrovert, introvert, andambivert to conduct in-depth interviews. The results of the research show that the percentage of students' critical thinking abilities has personality extrovert is 27.31%, namely in the low category. Percentage of students' critical thinking abilities with personality introvert is 57.54%, namely in the medium category. Percentage of students' critical thinking abilities with personality ambivert is 50.23%, namely in the medium category. The research results also show that students have personality extrovert with critical thinking skills in the medium category can go through the clarification and assessment stages while students with personality extrovert Low categories tend to only go through the clarification stage. Personality students introvert with high category critical thinking skills tend to go through the stages of clarification, assessment, strategy and conclusion. Then students have personality introvert Medium categories tend to go through the clarification and strategy stages. Meanwhile, students have personality introvert those in the low category tend to only go through the clarification stage. Personality students ambivert with high category critical thinking skills tend to go through the stages of clarification, assessment, strategy and conclusion. Then students have personality ambivert Medium categories tend to go through the clarification and strategy stages. Meanwhile, students have personality ambivert Low categories tend to only go through the clarification stage